Antioxidant Activity of Bioproduced Endophytic Fusarium Sp. HSFP-3 from Sijangkang Plant (Hornstedtia scyphifera Var. fusiformis) - Koraag, Alfa Michael Gabriel; Farida, Yunahara; Tarigan, Elsera Br.; Efendy, Oscar; Agusta, Andria; Simanjuntak, Partomuan (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
Endophytic mold Fusarium sp. HSFP-3 is one of the endophytic molds isolated from Sijangkang plants (Hornstedtia scyphyfera var. fusiformis). The purpose of this study is to conduct bioproduction, and test the antioxidant activity of bioproduced extracts and identify active fractions that have antioxidant activity. The research method started from the cultivation of endophytic mold HSFP-3 on PDB media for 21 days, the bioproduction results were extracted using ethyl acetate and acetone solvents. Antioxidant activity of HSFP-3 extract was determined by IC50 and AAI values, using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method. Isolation of antioxidant active fraction was carried out by column chromatography method using sephadex LH-20 stationary phase and silica. Isolation of antioxidant active compounds of HSFP-3 extract using bioautography guided assay approach with TLC-DPPH Bioautography method. The antioxidant test results of HSFP-3 extract has moderate activity with IC50 value 74,64 and AAI 0,844. Fraction 2.4 is an active fraction that has spot compounds with higher yellow color intensity compared to other fractions. Spot with Rf 0.35 in fraction 2.4 has a dark zone under UV 254 light. has a sea blue color under UV 366 light and a dark purple color after with Vanillin-Sulfate reagent